Near-zero thermal expansion etalon and preparation method and application thereof

By preparing near-zero thermal expansion standard devices for PbO, TiO2, and SrO, the problem of difficult to provide near-zero thermal expansion standard substances covering market demand in the prior art is solved, and stable thermal expansion performance in the range of 0 to 200°C is achieved, meeting the needs of high-precision expansion instruments.

CN119638408AActive Publication Date: 2025-03-18NATIONAL INSTITUTE OF METROLOGY CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411946634.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to provide near-zero thermal expansion standard substances that cover the domestic thermal expansion instrument market demand, and traditional low-expanding materials have problems of stability and processing difficulty in actual applications.

Method used

By placing PbO, TiO2, SrO in a ball milling tank for ball milling and calcining, followed by press molding, sintering and secondary sintering, a near-zero thermal expansion standard with a thermal expansion coefficient of 10-7 to 10-8/°C was prepared.

Benefits of technology

It achieves stable thermal expansion performance in the range of 0 to 200°C, meets the needs of high-precision expanders, and provides a reliable near-zero thermal expansion standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638408A_ABST
    Figure CN119638408A_ABST
Patent Text Reader

Abstract

The invention discloses a near-zero thermal expansion standard device and a preparation method and application thereof, and belongs to the technical field of measurement standard devices. The invention provides a preparation method of a near-zero thermal expansion etalon, which comprises the following steps: placing PbO, TiO2 and SrO in a ball milling tank for first ball milling, and then calcining to obtain calcined powder; and carrying out second ball milling on the obtained calcined powder, and then carrying out compression molding, sintering, third ball milling and second sintering to obtain the near-zero thermal expansion standard device. A solid phase method is used, a perovskite lattice structure is regulated and controlled through an A-site doped lead titanate material system so as to change the thermal expansion performance, meanwhile, Sr doped lead titanate is adopted, the negative linear expansibility of the standard is weakened, and preparation of the near-zero expansion standard is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metrological standards, and in particular relates to a near-zero thermal expansion standard and a preparation method and application thereof. Background Art

[0002] Solid materials usually expand and contract with temperature changes. However, changes in material volume with temperature can reduce the structural stability and safety reliability of precision components, and even destroy the functional properties of the material. In high-tech fields such as optical instruments, microelectronics, aerospace, etc., there is an urgent need for materials whose shape and size do not change with temperature to ensure that their components have high dimensional stability, precision and long service life. This has led to a demand for the research and development of near-zero expansion functional materials. The coefficient of thermal expansion (CTE) is an important parameter for characterizing the thermal expansion properties of materials. The development of near-zero expansion materials has put forward high requirements for the measurement and characterization of CTE. The development of near-zero thermal expansion standards is the basis for accurate measurement of thermal expansion instruments, and is also a necessary support for the processing and application of near-zero expansion materials.

[0003] The instruments currently used to measure CTE mainly include thermomechanical analyzers and thermal expansion instruments. Their working principle is to continuously measure the size of the sample under program temperature control conditions and calculate the CTE value through the numerical relationship between the size and temperature. Such instruments need to be calibrated and the method confirmed using a standard instrument or standard material at the beginning of the measurement to ensure the accuracy, consistency and traceability of the results. -7 ~10 -8 / ℃ level) material standards can effectively solve the daily calibration problems of thermal expansion instruments and provide traceability support and technical guarantee for the subsequent application of related metrological equipment in the field of material analysis and testing.

[0004] The research on near-zero thermal expansion standards has a long history, but there are still few reports on the release of linear expansion standard materials. Abroad, only the National Institute of Standards and Technology of the United States has released a thermal expansion coefficient standard material based on borosilicate glass material. In 2024, the China National Institute of Metrology released two new thermal expansion coefficient standard materials (high-purity aluminum and polyetheretherketone). Among them, high-purity aluminum is purchased from Alfa, which is easily subject to foreign trade import and export restrictions. In addition, due to the lack of core technology related to product development, the stability of subsequent products is difficult to guarantee; at the same time, the thermal expansion coefficients reported by these two standard materials are on the order of 10 -6 / ℃, which cannot meet the current domestic market demand for thermal expansion instruments. Traditional low expansion materials, such as Invar alloy, have a large specific gravity and a small linear expansion range; zero expansion glass-ceramics are brittle and difficult to process. These characteristics severely limit their practical applications.

[0005] Therefore, there is an urgent need for a near-zero thermal expansion standard to solve the above problems. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a near-zero thermal expansion standard and a preparation method and application thereof.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a near-zero thermal expansion standard, comprising the following steps:

[0009] (1) placing PbO, TiO2, and SrO in a ball mill for first ball milling, and then calcining to obtain calcined powder;

[0010] (2) The calcined powder obtained in step (1) is subjected to a second ball milling, followed by pressing, sintering, a third ball milling and a second sintering to obtain the near-zero thermal expansion standard.

[0011] Preferably, in step (1), the molar ratio of PbO, TiO2 and SrO is 1:1:x, where x=0.05, 0.1, 0.15 or 0.2.

[0012] Preferably, in step (1), the calcination temperature is 450-600° C., and the calcination holding time is 10 h.

[0013] Preferably, in step (2), the pressing pressure is 30 MPa.

[0014] Preferably, in step (2), the sintering temperature is 1050-1200° C., and the sintering holding time is 5 hours.

[0015] Preferably, in step (2), the temperature of the secondary sintering is 1050-1200° C., and the holding time of the secondary sintering is 5 hours.

[0016] Preferably, in step (2), a grinding step is also included after sintering.

[0017] Preferably, in step (1) or (2), the grinding balls of the first ball mill, the second ball mill and the third ball mill are all agate balls, the ball-to-material ratio is 2:1, the ball milling time is 24 hours, and the ball milling medium is all anhydrous ethanol.

[0018] The present invention provides a near-zero thermal expansion standard prepared by the preparation method described in the above technical solution, wherein the thermal expansion coefficient of the near-zero thermal expansion standard is 10 -7 ~10 -8 / ℃.

[0019] The present invention also provides the application of the near-zero thermal expansion standard described in the above technical solution in a high-precision expansion instrument.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects:

[0021] The present invention uses a solid-phase method to control the perovskite lattice structure by doping the A-site lead titanate material system to change the thermal expansion performance. Lead titanate has excellent properties such as a large negative linear expansion coefficient, a high Curie temperature, and a large spontaneous polarization. As an excellent ceramic oxide, it shows the potential for the development of near-zero expansion standard materials. At the same time, by using Sr to dope lead titanate, its negative linear expansion is weakened, thereby realizing the preparation of a near-zero expansion standard.

[0022] The near-zero thermal expansion standard provided by the invention has stable thermal expansion performance within the range of 0 to 200°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0024] Figure 1 This is a thermal expansion performance curve of the near-zero thermal expansion standard prepared in Example 3;

[0025] Figure 2 A physical picture of the near-zero thermal expansion standard prepared by the present invention;

[0026] Figure 3 XRD diagram of the near-zero thermal expansion standard prepared in Examples 1 to 4;

[0027] Figure 4 These are SEM images of the near-zero thermal expansion standards prepared in Examples 1 to 4. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] The embodiment of the present invention provides a method for preparing a near-zero thermal expansion standard, comprising the following steps:

[0031] (1) placing PbO, TiO2, and SrO in a ball mill for first ball milling, and then calcining to obtain calcined powder;

[0032] (2) The calcined powder obtained in step (1) is subjected to a second ball milling, followed by pressing, sintering, a third ball milling and a second sintering to obtain the near-zero thermal expansion standard.

[0033] In a preferred embodiment, in step (1), the ratio of the amount of PbO, TiO2, and SrO is 1:1:x, where x=0.05, 0.1, 0.15, or 0.2. The present invention adjusts the thermal expansion coefficient of the thermal expansion standard by controlling the amount of SrO. Too little SrO has little effect on lattice distortion, and thus cannot improve thermal expansion performance, while too much SrO may cause the destruction of the original perovskite lattice structure and lose the negative expansion correction property; using SrO as the Sr source can avoid the generation of other additional products (such as SrCO3 may generate complex carbides during the sintering process).

[0034] In a preferred embodiment, in step (1), the grinding balls of the first ball mill are agate balls, the ball-to-material ratio is 2:1, the ball milling time is 24 hours, and the ball milling medium is anhydrous ethanol. The present invention can fully mix the raw materials and reduce the size of the raw materials through the first ball milling, which is conducive to the full reaction between the raw materials in the subsequent sintering process; the use of agate balls has the advantages of high wear resistance and no pollution, and the use of anhydrous ethanol as the ball milling medium has the advantages of environmentally friendly raw materials, easy to obtain, and low toxicity.

[0035] In a preferred embodiment, the first ball milling step further comprises a heating step, wherein the heating step specifically comprises: pouring the slurry obtained by the first ball milling into a beaker, and then placing the slurry on a magnetic stirrer for heating and stirring; the heating and stirring temperature is 50° C. The present invention volatilizes the ethanol by heating.

[0036] In a preferred embodiment, in step (1), the calcination temperature is 450-600°C, the calcination holding time is 10 hours, the calcination atmosphere is air, and the calcination equipment is a muffle furnace. The present invention activates the raw materials by calcination and performs a pre-reaction at the same time.

[0037] In a preferred embodiment, in step (2), the pressure of the pressing process is 30 MPa; the diameter of the product obtained by the pressing process is 10 mm and the thickness is 2 mm.

[0038] In a preferred embodiment, in step (2), the sintering temperature is 1050-1200° C., the sintering holding time is 5 hours, and the sintering atmosphere is air.

[0039] In a preferred embodiment, in step (2), the secondary sintering temperature is 1050-1200°C, the secondary sintering holding time is 5 hours, and the secondary sintering atmosphere is air. The present invention is conducive to obtaining a near-zero thermal expansion standard with high uniformity and stable performance through secondary sintering.

[0040] In a preferred embodiment, in step (2), a grinding step is further included after sintering; the grinding tool is fine sandpaper. The present invention removes the surface part of the product obtained by secondary sintering by grinding, and retains the middle layer part to ensure the uniformity of the sample.

[0041] In a preferred embodiment, in step (2), the grinding balls of the second ball mill and the third ball mill are agate balls, the ball-to-material ratio is 2:1, the ball milling time is 24 hours, and the ball milling medium is anhydrous ethanol.

[0042] The present invention provides a near-zero thermal expansion standard prepared by the preparation method described in the above technical solution, wherein the thermal expansion coefficient of the near-zero thermal expansion standard is 10 -7 ~10 -8 / ℃.

[0043] In a preferred embodiment, the composition of the near-zero thermal expansion standard is Pb 1-x Sr x TiO3, wherein x=0.05, 0.1, 0.15 or 0.2.

[0044] The present invention also provides the application of the near-zero thermal expansion standard described in the above technical solution in a high-precision expansion instrument.

[0045] The room temperature in the embodiments of the present invention refers to "25±2°C".

[0046] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0047] Example 1

[0048] A method for preparing a near-zero thermal expansion standard, the specific steps are as follows:

[0049] (1) The raw materials PbO, TiO2 and SrO are placed in glass containers respectively, and then placed in a vacuum oven at 100°C for drying for 24 hours. After cooling, they are transferred to a drying dish for standby use. PbO, TiO2 and SrO are weighed using an electronic balance according to a molar ratio of 1:1:0.05, and then placed in a polytetrafluoroethylene ball mill, with anhydrous ethanol as the ball milling medium and agate balls as the grinding balls, and a ball-to-material ratio of 2:1. The ball mill is used for 24 hours using a planetary ball mill, and then the slurry obtained by ball milling is poured into a beaker, and the beaker is placed on a magnetic stirrer and heated and stirred at 50°C. After the ethanol evaporates, a mixed powder is obtained.

[0050] (2) The mixed powder obtained in step (1) is placed in an alumina crucible, and the alumina crucible is placed in a muffle furnace and kept at 500° C. for 10 h to obtain a calcined powder.

[0051] (3) The calcined powder obtained in step (2) is placed in a planetary ball mill, with anhydrous ethanol as the ball milling medium and agate balls as the grinding balls at a ball-to-material ratio of 2:1, and the ball milling is performed for 24 hours. The slurry obtained by ball milling is then poured into a beaker, and the beaker is placed on a magnetic stirrer and heated and stirred at 50° C. After the ethanol evaporates, the powder obtained by ball milling is placed on a tablet press and pressed into a ceramic sheet with a diameter of 10 mm and a thickness of 2 mm at a pressure of 30 MPa.

[0052] (4) The ceramic sheet obtained in step (3) is sintered at 1100° C. for 5 h. After cooling, the surface of the ceramic sheet is polished off with fine sandpaper, and the middle layer is retained. The ceramic sheet is then ball-milled into powder using a planetary ball mill (using anhydrous ethanol as the ball milling medium, agate balls as the grinding balls, a ball-to-material ratio of 2:1, and a ball milling time of 24 h). The ceramic sheet is then sintered at 1100° C. for 5 h to complete secondary sintering to obtain a near-zero thermal expansion standard, which is recorded as 1:1:0.05.

[0053] Example 2

[0054] The difference from Example 1 is that in step (1), PbO, TiO2 and SrO are weighed according to the material amount ratio of 1:1:0.1, and the remaining steps are the same as Example 1, recorded as 1:1:0.1.

[0055] Example 3

[0056] The difference from Example 1 is that in step (1), PbO, TiO2 and SrO are weighed according to the material amount ratio of 1:1:0.15, and the remaining steps are the same as Example 1, recorded as 1:1:0.15.

[0057] Example 4

[0058] The difference from Example 1 is that in step (1), PbO, TiO2 and SrO are weighed according to the material amount ratio of 1:1:0.2, and the remaining steps are the same as Example 1, recorded as 1:1:0.2.

[0059] Example 5

[0060] The difference from Example 1 is that in step (4), the ceramic sheet obtained in step (3) is sintered at 1200° C. for 5 h, and the remaining steps are the same as Example 1.

[0061] Example 6

[0062] The difference from Example 1 is that in step (4), the ceramic sheet obtained in step (3) is sintered at 1180° C. for 5 h, and the remaining steps are the same as Example 1.

[0063] Example 7

[0064] The difference from Example 1 is that in step (4), the secondary sintering is completed by sintering at 1150° C. for 5 hours, and the remaining steps are the same as Example 1.

[0065] Example 8

[0066] The difference from Example 1 is that in step (4), the secondary sintering is completed by sintering at 1050° C. for 5 hours, and the remaining steps are the same as Example 1.

[0067] Example 9

[0068] The difference from Example 1 is that in step (2), the temperature is kept at 550° C. for 10 h, and the remaining steps are the same as Example 1.

[0069] Example 10

[0070] The difference from Example 1 is that in step (2), the temperature is kept at 450° C. for 10 h, and the remaining steps are the same as Example 1.

[0071] Comparative Example 1

[0072] The difference from Example 1 is that in step (1), PbO, TiO2 and SrO are weighed according to the material ratio of 1:1:0.02, and the remaining steps are the same as Example 1.

[0073] Comparative Example 2

[0074] The difference from Example 1 is that in step (1), PbO, TiO2 and SrO are weighed according to the material ratio of 1:1:0.25, and the remaining steps are the same as Example 1.

[0075] Comparative Example 3

[0076] The difference from Example 1 is that in step (4), the ceramic sheet obtained in step (3) is sintered at 900° C. for 5 h, and the remaining steps are the same as Example 1.

[0077] Comparative Example 4

[0078] The difference from Example 1 is that in step (4), the secondary sintering is completed by sintering at 1300° C. for 5 hours, and the remaining steps are the same as Example 1.

[0079] Comparative Example 5

[0080] The difference from Example 1 is that in step (4), the secondary sintering is completed by sintering at 1100° C. for 2 hours, and the remaining steps are the same as Example 1.

[0081] Comparative Example 6

[0082] Steps (1) to (3) are the same as in Example 1;

[0083] (4) The ceramic sheet obtained in step (3) is ground with fine sandpaper to remove the surface portion of the ceramic sheet, retaining the middle layer portion, and then the ceramic sheet is ball-milled into powder using a planetary ball mill (using anhydrous ethanol as the ball-milling medium, agate balls as the grinding balls, a ball-to-material ratio of 2:1, and a ball-milling time of 24 h), and then sintered at 1100° C. for 5 h to obtain a near-zero thermal expansion standard.

[0084] The thermal expansion coefficient of the thermal expansion standards prepared in Examples 1 to 10 and Comparative Examples 1 to 6 was tested with reference to the thermal expansion coefficient calibration method of NIM-ZY-CD-LX-118 material. The specific testing process is as follows: using the laser interferometry method, the expansion or contraction of the measured object causes the change of the optical path difference to cause the movement of the stripes, the change of the stripes is detected, and the change in the stripe length is recorded; according to the selected temperature range, the temperature value of the measured object and the laser interferometer reading are recorded at each temperature point, and the instantaneous thermal expansion coefficient of the measured object when the reference temperature is 20°C is calculated. The results are shown in Tables 1 and 2.

[0085] Table 1 Thermal expansion coefficients of thermal expansion standards prepared in Examples 1 to 10 and Comparative Examples 1 to 6 at 200°C

[0086] <![CDATA[Coefficient of thermal expansion (1×10 -8 / °C)]]> Example 1 20.53 Example 2 14.47 Example 3 9.84 Example 4 11.52 Example 5 10.11 Example 6 10.03 Example 7 9.97 Example 8 11.89 Example 9 12.37 Example 10 15.79 Comparative Example 1 60.53 Comparative Example 2 80.64 Comparative Example 3 -40.22 Comparative Example 4 110.51 Comparative Example 5 180.11 Comparative Example 6 100.74

[0087] It can be seen from Table 1 that the thermal expansion coefficients of the thermal expansion standards prepared in Examples 1 to 10 of the present invention are all close to 10 at 200°C. -8 The thermal expansion coefficient of the thermal expansion standard prepared in Comparative Examples 1 to 6 is as high as 10 -6 Even in comparative example 3 (when the sintering temperature is too low), negative expansion occurs.

[0088] Table 2 Thermal expansion coefficient test data of thermal expansion standard prepared in Example 3

[0089]

[0090]

[0091] Figure 1 This is a thermal expansion performance curve of the near-zero thermal expansion standard prepared in Example 3. Figure 1 As can be seen from Table 2, the CTE level of the near-zero thermal expansion standard prepared in Example 3 is 10 at 0-200°C. -8 / ℃, approaching to 0; with the increase of measuring temperature, the CTE value of the standard device remains basically unchanged, indicating that the thermal expansion performance of the standard device is stable.

[0092] Figure 2 A physical picture of the near-zero thermal expansion standard prepared by the present invention.

[0093] Figure 3 The XRD diagram of the near-zero thermal expansion standard prepared in Examples 1 to 4 is shown in FIG. Figure 3 It can be seen that the near-zero thermal expansion standard prepared by the present invention is composed of Pb 1-x Sr x Composition of TiO3. Figure 3 It can be found from the middle dotted line that as the Sr doping concentration increases, the characteristic peak shifts to a larger angle, indicating that the higher the doping concentration, the smaller the lattice spacing becomes, that is, Sr atoms are mainly inserted into the perovskite lattice, which is also consistent with the stoichiometric ratio of the components of the present invention.

[0094] Figure 4 The SEM images of the near-zero thermal expansion standards prepared in Examples 1 to 4 are shown below. Figure 4 It can be seen that the surface of the near-zero thermal expansion standard prepared in Example 3 is the most uniform and has basically no holes.

[0095] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a near-zero thermal expansion standard, characterized in that: The following steps are involved: (1) placing PbO, TiO2, and SrO in a ball mill for first ball milling, and then calcining to obtain calcined powder; (2) The calcined powder obtained in step (1) is subjected to a second ball milling, followed by pressing, sintering, a third ball milling and a second sintering to obtain the near-zero thermal expansion standard.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of PbO, TiO2 and SrO is 1:1:x, where x=0.05, 0.1, 0.15 or 0.

2.

3. The preparation method according to claim 1, characterized in that: In step (1), the calcination temperature is 450-600° C., and the calcination holding time is 10 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the pressing pressure is 30 MPa.

5. The preparation method according to claim 1, characterized in that: In step (2), the sintering temperature is 1050-1200° C., and the sintering holding time is 5 hours.

6. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the secondary sintering is 1050-1200° C., and the insulation time of the secondary sintering is 5 hours.

7. The preparation method according to claim 1, characterized in that: In step (2), a grinding step is also included after sintering.

8. The preparation method according to claim 1, characterized in that: In step (1) or (2), the grinding balls of the first ball mill, the second ball mill and the third ball mill are all agate balls, the ball-to-material ratio is 2:1, the ball milling time is 24 hours, and the ball milling medium is all anhydrous ethanol.

9. A near-zero thermal expansion standard prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The thermal expansion coefficient of the near-zero thermal expansion standard is 10 -7 ~10 -8 / ℃.

10. Use of the near-zero thermal expansion standard according to claim 9 in a high-precision expansion instrument.

Citation Information

Patent Citations

  • Zero-expansion material

    CN101070244A

  • Preparation method of zero expanding material with multiferroic and high mechanical properties

    CN101798225A

  • Adjustable thermal expansion material (KMn) xA2-xMo3O12 and preparation method thereof

    CN118996629A